The Effectiveness of Brisk Walking Intervention Through Comic Book Education on Self-Efficacy and HbA1c Control in Type 2 Diabetes Mellitus Patients in Rural Area at Takalar Regency - Zainuddin, Zainuddin; Ernawati, Ernawati; Yuniar, Yuniar; Aswadi, Aswadi; Liputo, Gusti Pandi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Poor self-efficacy and inability to control blood sugar (HbA1c) are special concerns in achieving structured self-management. Meanwhile, the use of educational media such as Comic book is a solution to improve the self-management of diabetes mellitus patients. Therefore, this research aimed to assess the effectiveness of comic book: BW (Brisk Walking) on ​​self-efficacy and HbA1C control in type 2 diabetes mellitus (T2DM) patients in Takalar Regency. A quantitative method was used with a Quasi-Experimental two-group pre-post test design. The respondents were divided into two groups, namely Group 1 given comic Book: BW with WhatsApp Group monitoring, and Group 2 which received a similar intervention but without monitoring. A total of 60 respondents, 30 in each group were selected using the purposive sampling method, while data collection was carried out using the Exercise Self-Efficacy Scale (ESES) questionnaire consisting of 16 questions. Moreover, data analysis was conducted the T-test with a significance value of p<0.05. The results showed that the administration of comic book: BW significantly affected self-efficacy and HbA1c Control with p=0.000. BW caused a significant increase in self-efficacy and a decrease in HbA1c Control. This intervention has the potential to improve facilitate health workers and the patient self-management of type 2 diabetes mellitus through providing comic books.